2011
DOI: 10.1111/j.1346-8138.2010.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of cutaneous adverse drug reactions

Abstract: Drug-induced hypersensitivity reactions are of major medical concern because they are associated with high morbidity and high mortality. In addition, individual patients' reactions are impossible to predict in each patient. In the field of severe cutaneous adverse drug reactions (cutaneous ADR) such as Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug-induced hypersensitivity syndrome (DHIS) or drug rash with eosinophilia and systemic symptoms (DRESS), major advances have recently been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 45 publications
1
48
0
2
Order By: Relevance
“…Current studies indicate that HLAB*1502 is a marker for carbamazepine-induced SJS⁄TEN in Southeast Asian popula ons, where the prevalence of HLA-B*1502 is rela vely high. 22 The role of cor costeroids in the treatment of SJS/TEN is controversial. Earlier studies suggested increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies indicate that HLAB*1502 is a marker for carbamazepine-induced SJS⁄TEN in Southeast Asian popula ons, where the prevalence of HLA-B*1502 is rela vely high. 22 The role of cor costeroids in the treatment of SJS/TEN is controversial. Earlier studies suggested increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a significant amount of interest in HLA variants, particularly since genome-wide association studies have revealed associations between specific HLA alleles and drug hypersensitivity responses, e.g. abacavir/HLA-B*5701, allopurinol/HLA-B*5801, and carbamazepine HLA-B*1502 (Aihara, 2011;Wei et al, 2012). Recent studies have demonstrated that, in the case of abacavir, binding of abacavir to the peptide binding cleft of the HLA can alter the peptide repertoire presented to T-cells, which can result in an allogenic-like reaction (Illing et al, 2012;Norcross et al, 2012;Ostrov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, certain human leukocyte antigens (HLA) have been associated with delayed drug sensitivity to which the Food and Drug Administration (FDA, USA) has responded by recommending testing for specific HLA genes for carbamazepine and abacavir [59]. The variant HLA gene that can lead to a life threatening skin disorder when taking carbamazepine is primarily present in people from Asian countries and is virtually absent in people without Asian ancestry [60]. Thus, those physicians who perceive racial inequality may be cognizant of these issues.…”
Section: Discussionmentioning
confidence: 99%